2013
DOI: 10.1371/journal.pone.0065505
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Central Administration of Ghrelin Increases Bone Mass through a Mechanism Independent of Appetite Regulation

Abstract: Leptin plays a critical role in the central regulation of bone mass. Ghrelin counteracts leptin. In this study, we investigated the effect of chronic intracerebroventricular administration of ghrelin on bone mass in Sprague-Dawley rats (1.5 μg/day for 21 days). Rats were divided into control, ghrelin ad libitum-fed (ghrelin ad lib-fed), and ghrelin pair-fed groups. Ghrelin intracerebroventricular infusion significantly increased body weight in ghrelin ad lib-fed rats but not in ghrelin pair-fed rats, as compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Apart from its orexigenic effect, research in the last decade has shown that ghrelin has regulatory roles in in many organs and systems (13). Ghrelin signaling has increasingly been recognized as a key regulator of obesity, insulin resistance and diabetes; intriguingly, many of these regulatory functions appear to be independent of ghrelin's effect on food intake (48). This current review is focused on the most recent findings of ghrelin in glucose homeostasis (911), energy-homeostasis (7, 12), heart disease (1316), muscular atrophy (17, 18), bone metabolism (8, 19, 20), and cancer development/progression (21, 22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from its orexigenic effect, research in the last decade has shown that ghrelin has regulatory roles in in many organs and systems (13). Ghrelin signaling has increasingly been recognized as a key regulator of obesity, insulin resistance and diabetes; intriguingly, many of these regulatory functions appear to be independent of ghrelin's effect on food intake (48). This current review is focused on the most recent findings of ghrelin in glucose homeostasis (911), energy-homeostasis (7, 12), heart disease (1316), muscular atrophy (17, 18), bone metabolism (8, 19, 20), and cancer development/progression (21, 22).…”
Section: Introductionmentioning
confidence: 99%
“…This study has significant therapeutic implications, suggesting that elderly osteoporosis patients may benefit from ghrelin therapy. Most recently, a study in rats shows that chronic central administration of ghrelin increases bone mass independent of food intake or weight gain (8). A study in healthy elderly women shows positive correlation between serum ghrelin and trabecular BMD, using quantitative CT (50).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was reported that ghrelin also regulates bone remodeling through GHS-R in osteoblasts by modulating the cAMP response element binding protein (CREB) and runt-related transcription factor 2 (Runx2) pathways in mice (71). Moreover, chronic central administration of ghrelin increases bone mass through a mechanism that is independent of body weight, suggesting that ghrelin may have a bone anabolic effect through the central nervous system (72). On the other hand, ghrelin infusion has no acute effect on markers of bone turnover in healthy controls and post-gastrectomy subjects, which are prone to osteropenia and osteomalacia, but is inversely correlated with bone resorption (73).…”
Section: Effects On the Bonementioning
confidence: 99%
“…These late-onset leptin-dependent changes in bone resorption in Ghrs À / À mice suggested the possible involvement of cocaine amphetamine regulated transcript (CART), a hypothalamic neuropeptide known to stimulate bone resorption in leptin-deficient mice 27 and the regulation of bone mass in humans. 28 Recently, Choi et al 29 examined the effects of chronic intracerebroventricular injection of ghrelin on bone metabolism in rats. This study demonstrated that chronic central administration of ghrelin had an anabolic effect on bone mass.…”
Section: Ghrelinmentioning
confidence: 99%
“…This study demonstrated that chronic central administration of ghrelin had an anabolic effect on bone mass. 29 Although the mechanism for central ghrelin action was not determined, it was postulated that increased ghrelin activity within the brain was suppressing the sympathetic nervous system (SNS), which is ordinarily regulated by leptin levels, and thus reducing bone mass. 29 Therefore, central signalling pathways are implicated in regulating the actions of ghrelin on bone.…”
Section: Ghrelinmentioning
confidence: 99%